Design, synthesis, and evaluation of new series of Imperatorin analogs with potential vasodilatory activity. Issue 1 (2nd January 2019) - Hou, Ya-Jing; Wang, Cheng; Wang, Tao; Huang, Li-Min; Lin, Yuan-Yuan; He, Huai-Zhen
Abstract: Two series of imperatorin analogs were synthesized based on our previous research and evaluated for their vasodilatation activities on in vitro rat mesenteric artery, basilar artery, and renal artery ring models. Target compounds were characterized by infrared, 1 H NMR, and mass spectra. Most derivatives possessed significant vasodilatory activity on the mesenteric artery, and compound3a exhibited favorable and broad vasodilatation activities on three kinds of rat artery ring models. The pharmacological results indicated that introducing nitrogen-contained ring in side chain or large steric hindrance at the distal end could increase the vasodilatory activity. Further, replacement of oxygen atom (–O–) in the skeleton of furocoumarin derivatives with nitrogen (–NH–) could cause the decrease of vasodilatory activity. The molecular docking also indicated that compound3a showed a best affinity with α-1C receptor (PDB ID: 3G43). All these results suggested compound3a would be a potential vasodilatory agent for hypertension. Abstract :